Application of Quality Control Circle Method in Crusher Knife Reconditioning Products (Case Study in PT. Andritz Pekanbaru) - Samuel Putra Tambunan; Anita Susilawati; Yohanes Yohanes (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2020)
The purpose of this study is to identify, analyze and evaluate the influencing of defects factors at the crusher knife reconditioning process in PT Andritz Pekanbaru. In this research adopted the Quality Control Circle (QCC) method. The QCC method is a quality control that is focused on the process of Plan, Do, Check, Action (PDCA). The research was carried out with 8 stages of PDCA, namely determining the theme, determining the title, finding the source of the problem, solving the problem plan, implementing, evaluating, standardizing, and determining the next plan. After observing the crusher knife reconditioning process, there were 10 defects that occurred in the crusher knife reconditioning process, which were porosity of 673 cases, curling tip of 78 cases and 57 of fewer cases followed. The repairs were carried out using the QCC method. The results of improvements were proved by reducing of the percentage of total defect porosity from 13% to 2%. Therefore, the repairs were successfully implementation, which decreasing of the defect porosity of 11%.